Cortical Alpha Oscillations Predict Speech Intelligibility - Dimitrijevic, Andrew; Smith, Michael L.; Kadis, Darren S.; Moore, David R. (Frontiers in Human Neuroscience, 2017)
Previous work has shown that brain oscillations, particularly alpha rhythms (8-12 Hz) play important roles in sensory processes involving working memory and attention. In recent years, the role of cognition (working memory and attention) has been increasingly appreciated in speech in noise perception. However, no previous study has examined brain oscillations during performance of a continuous speech perception test. The aim of this study was to measure cortical alpha rhythms during attentive listening in a commonly used speech in noise task (digits-in-noise, DiN) to better understand the neural processes associated with “top-down” cognitive processing in adverse listening environments. We recruited 14 normal hearing young adults. DiN speech reception threshold (SRT) was measured in an initial behavioral experiment. EEG activity was then collected (i) while performing the DiN near SRT, and (ii) while attending to a silent, close-caption video during presentation of identical digit stimuli that the participant was instructed to ignore. Three main results were obtained: (1) during attentive (‘active’) listening to the DiN, a number of distinct neural oscillations were observed (mainly alpha with some beta; 15-30 Hz). No stimulus induced oscillations were observed during attention to the video (‘passive’ listening); (2) overall, alpha event-related synchronization (ERS) of central/parietal sources were observed during active listening when data were grand averaged across all participants. In some participants, a smaller magnitude alpha event-related desynchronization (ERD), originating in temporal regions, was observed; (3) when individual EEG trials were sorted according to correct and incorrect digit identification, the temporal alpha ERD was consistently greater on correctly identified trials. No such consistency was observed with the central/parietal alpha ERS. These data demonstrate that changes in alpha activity are specific to listening conditions. To our knowledge, this is the first report that shows almost no brain oscillatory changes during a passive task compared to an active task in any sensory modality. Temporal alpha ERD was related to correct digit identification.